Broaden the applications of peptidyl asparaginyl ligases - Xia, Yiyin (Nanyang Technological University, 2023)
Peptidyl asparaginyl ligases (PALs) are highly active enzymes that catalyse peptide ligation reactions through transpeptidation. To further increase the utility of PALs, I have successfully designed an unnatural analogue of asparagine, Asn(OH), as the P1 substrate of these ligases. Using Asn(OH)-mediated cyclization, a new class of cyclic peptides containing Asn(OH) as the key pharmacophore have been generated, some of which are potent inhibitors of matrix metalloproteinase 2 (MMP2). The Asn(OH) residue can also be easily converted to Asp in a mild oxidation reaction. Furthermore, I have also established a method to overcome the reversibility of PAL-mediated ligation by coupling it to glutaminyl cyclase-catalyzed pyroglutamyl formation which quenches the released leaving group. Using this cascade enzymatic scheme, the PAL-mediated ligation can achieve near-quantitative yields even at an equal molar ratio between two large ligation partners. To conclude, my work has improved the efficiency of PAL-mediated ligation and broadened its application scope.